Developing Interactive Learning Media for Narrative Texts at SMK - Refni Novela; Atni Prawati; Masyhur Masyhur (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The objective of this research is to develop interactive learning media for narrative texts at SMK Telkom Pekanbaru and to know the validity of interactive learning media for narrative at SMK Telkom Pekanbaru. This research used research and development method. This development used type of research is ADDIE model. Data analysis technique in this research used needs analysis questionnaire and expert judgment questionnaire by material expert and media expert. The result of the research shows that the range of mean obtained from the material expert is 4.3 meanwhile from the media expert is 4.4. They fall into the “very good” category. The result indicates that the interactive learning media is appropriate to be used for the 10th Grade Students of SMK TELKOM Pekanbaru.  The use of interactive learning media has motivated and helped students in the learning process, especially in reading narrative texts. students can learn independently in a fun way. They no longer feel bored in the process of learning to read.